Comparative analysis of 2 vs 2 and 3 vs 3 small-sided games on technical skills development in youth basketball players - Mahyudi, Y. V. (European Journal of Human Movement, 2025)
This study aimed to compare the effectiveness of 2vs2 and 3vs3 small-sided games (SSG) formats in developing technical and tactical skills among youth basketball players. Forty male athletes aged 12-15 years were randomly divided into two groups: SSG 2 vs. 2 (n = 20) and SSG 3 vs. 3 (n = 20). The intervention was conducted over 8 weeks with three sessions per week, using a standardized court size of 10x15 meters and modified game rules. Technical performance was assessed through multiple variables, including total passing, correct passing, assists, total shots, shot points, offensive rebounds, defensive rebounds, fouls, and turnovers. Results showed significant improvements in both formats with distinct characteristics. The 2vs2 format shows a significant increase in total passing (t = 10.30) and correct passing (t = 10.31), a significant increase in defensive rebounds (t = 10.17), and a decrease in turnovers. The 3vs3 format shows a more substantial increase in total passing (t = 17.439) and correct passing (t = 14.348), a significant increase in total shots (t = 9.375), and points scored (t = 5.405). Comparative analysis reveals that the 2vs2 format is more effective for developing individual skills and defensive abilities, while the 3vs3 format excels in team play development and offensive variation. These findings suggest that both formats serve complementary roles in player development, with the 2 vs. 2 format being particularly suitable for fundamental skill development and the 3 vs. 3 format for advancing team play concepts and offensive tactical understanding.